Performance of Solvent (Acetone-Butanol-Ethanol) Fermentation by Clostridwmsaccharobutyl/Cum Strain P262 and Ncimb8052 Using Free and Immobilized Cells System - Yaacob, Nor Suhaila (2003)
The performance of solvent (Acetone-butanol-ethanol) fermentation by two strains of Clostridium saccharobutylicum (P262 and NCIMB8052) were studied using different sizes of bioreactor (28 mL McCartney bortle, 0.5 L and 2 L stirred tank fermenter). The fermentations were carried out with batch process using freely suspended cells and immobilized cells system. Immobilization of cells was carried out. passively, using cubes of polyurethane foam as biomass support particles (BSP). To study the efficiency of cell immobilization. the variables investigated include pore size of BSP. BSP number and BSP size. The effect of chemical pretreatment on the efficiency of cell immobilization using BSP was investigated using activated carbon (charcoal) and glutaraldehyde. Among the chemical pretreatment applied to the BSP were 4% activated charcoal and 25% glutaraldehyde.The size of bi oreactor gave a signi ficance i nfluence on so l vent fermentati on performance by both solvent-prod ucing strai ns. The highest production of total sol vent ( 1 0.86 giL) and (8. 23 giL) by strain P262 and NCIM B8052 was obtained in 2 L fermenter us ing 50 giL gl ucose. respectively. In 0 . 5 L fermenter, production of total solvent was reduced to 7.99 giL and 7.17 giL for strain P262 and NCIM B8052, respectively. Further reducti on of total solvent was observed in fermentation using 28 mL McCartney bottle. Reducti on of solvent production was found to be associated with the activity of proteolytic enzyme (protease) detected in the culture during the fermentation. This proteolytic enzyme may be responsible in the degradation of enzyme involved in solvent fermentation, which in tum reduced solvent production significantly. Among the different types of starch investigated, com starch was the most susceptible to solvent production ( 1 5 .67 giL) by strain P262 followed by sago starch ( 1 4.54 giL), rice ( 1 0.2 1 giL), tapioca ( 8 . 84 giL) and potato (8.66 giL). In subsequent experiment to investigate the effect of sago starch concentration ( 1 0- 80 giL) on the performance of solvent fermentation, it was found that the highest solvent production ( 1 3 . 8 1 giL) was obtained at 50 giL sago starch. For fermentation using sago starch, the use of 2 L fermenter enhanced the solvent production by about 1 . 5 times higher as compared to 0.5 L fermenter ( 1 3. 1 6 giL). though the activity of amylolytic enzyme secreted did not significantly differ. When sago starch was used as a carbon source, very l ow solvent production ( 1 2.49 glL- 1 6. 87 giL) was obtained in all fermentations using strain NCIMB 8052. The highest efficiency of i m mobilization of cells of C saccharohuly/icum strain P262 and NCIMB8052 was achi eved by using 15 units/28 m! culture medium of I em3 BSP having 60 ppi. The BSP pretreated with 4% activated charcoal increased the effici ency of cell i m m obilization significantly as com pared to untreated B SP. On the other hand, BSP treated with glutaraldehyde was not singniticantly different as compared to untreated B S P . Fermentati on using i m m ob i l ized cells of strain P262 gave hi